Histórias de trabalhadores nortistas no Norte/ Noroeste do Paraná (1940/1970) - Medeiros, Adriana de Carvalho (2017)
This work aims to verify the experiences of the North American workers who participated in the process of re-occupation of the North / Northwest of Paraná between the 1940s and 1970s. Often the official history, based on an original myth with the idea of pioneering, tended to exclude Northerners workers from the narratives published by historiography. Although each narrative constructed by our characters, and by the analysis of the different sources has its specificities, it was possible to identify similarities and repetitions, which allowed us to infer about the possibilities and horizons presented to these workers. In this regard, we show that, unlike those Paulistas, Mineiros and Catarinenses, the elected officials of the official history, the Northerners, referred to a group of workers who shared peculiarities about their culture, but mainly a common class condition: they were the poorest workers who carried out the worst jobs, either in the clearing of the forest at the beginning of the process of capitalist occupation and land, or later in planting and agricultural production. In this sense, to understand the relationships and experiences lived in the period delimited, we also try to understand, the different forms and arrangements made between workers and owners, which did not always involve payment in cash. Our frame of reference is found in Marxism, since in analyzing the stories of the subjects portrayed here, we perceive how these constituted themselves as subjects, while producing materially. For this we start from the concept of experience of Edward Thompson, which allowed us to think about working relationships in the very making of the working class. In this work, the possibilities opened using Oral History were very important, since it allowed to include subjects that were frequently excluded from the records made by the Official History. In this regard, in narrating their stories and reconstructing memories about the past, several workers reworked and recomposed their experiences from the expectations placed in the present time. In the quest to find clues and evidence about the presence of the Northerners workers in the North / Northwest of Paraná, we also resort to documents that were usually ignored by positivist history, but which in the present time are considered important sources of information: ecclesial sources and autos produced by the Labor Court. It is at the intersection of the information and analysis of the sources that were collected during the research, that we were able to carry out a fabrication that allowed to verify the social dynamics, arrangements and agreements that were being constituted by these workers over time. Key- words: northey woekers. North/ Nortwest of Paraná. Oral History. Memory.